Fatores de risco para o near miss materno na atenção primária à saúde - Costa, Catiane Souza Tavares (2017)
Objective: Objective: To analyze risk factors for maternal Near Miss (NM) in post NM women, residing in Aracaju, related to primary health care. Method: Control case study with 54 women (18 cases and 36 controls). Quantitative variables were analyzed using the non-parametric Wilcoxon test. To evaluate the association between the categorical variables, the Chi-Square and Fisher's Exact tests were used. Risk factors were estimated from Odds Ratio (OR). Results: For the quantitative variables, the behavior between the case and control groups was similar. Among the qualitative variables "having a partner, the previous history of the disease and the type of delivery" were the variables that were statistically significant with NMM. In the logistic regression simple, for the analysis of risk factors for NMM, it was verified that having a partner and type of delivery presented, respectively, 13.60 (CI: 4.11, 4.96), 4.08 (CI: 1.23; 13,51) more chance of a woman having NMM. Conclusion: Continued attention is paid to women throughout the puerperal pregnancy cycle, since it has been identified that these